Detection of carbapenemases using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) meropenem hydrolysis assay - Hrabák, Jaroslav (Methods in molecular biology, 2015)
Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) has been recently introduced to many diagnostic microbiological laboratories. Besides the identification of bacteria and fungi, that technique provides a potentially useful tool for the detection of antimicrobial resistance, especially of that conferred by β-lactamases. Here, we describe an assay allowing a detection of meropenem hydrolysis in clinical isolates of Enterobacteriaceae, Pseudomonas spp., and Acinetobacter baumannii using MALDI-TOF MS. This method is able to confirm carbapenemases within 3 h. The results are important for proper and fast intervention to limit the spread of carbapenemase-producing bacteria and provide information for appropriate initial therapy of the infections caused by these microbes.
Keywords: biotest; Pseudomonas Infections; Pseudomonas; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; hydrolýza; beta-laktamasy; bakteriální proteiny; Bacterial Proteins; lidé; Anti-Bacterial Agents; beta-laktamová rezistence; Acinetobacter Infections; beta-Lactamases; Thienamycins; pseudomonádové infekce; thienamyciny; beta-Lactam Resistance; Hydrolysis; Biological Assay; Acinetobacter baumannii; exprese genu; spektrometrie hmotnostní - ionizace laserem za účasti matrice; antibakteriální látky; infekce bakteriemi rodu Acinetobacter; Gene Expression; Humans